Anti‐EpCAM Gold Nanorods and Femtosecond Laser Pulses for Targeted Lysis of Retinoblastoma. Issue 1 (23rd April 2018) - Katchinskiy, Nir; Godbout, Roseline; Hatef, Ali; Elezzabi, Abdulhakem Y.
Abstract: Retinoblastoma is a cancerous disease that affects the retina, and primarily affects young children. To date, the primary treatment goal of retinoblastoma is to save the child's life, while the preservation of the eye and its functionality are the secondary goals. Reoccurrence of tumors is mainly attributed to the persistence of cancer stem cells. EpCAM+ Y79 retinoblastoma cells behave like cancer stem cells and are recognized as cells that are resistant to treatment. We demonstrate an effective technique to treat retinoblastoma cancer cells, using femtosecond laser pulses and epithelial cell adhesion molecule (EpCAM)‐targeting gold nanorods (Au‐NRs). Complete assessment of the optimal laser parameters required for the development of a translational retinoblastoma cancer treatment is provided. Both an MTS cellular metabolism assay and a fluorescence viability assay demonstrate an astonishing cellular viability drop, to ≈10%. Right after laser irradiation the cellular membrane ruptures. Calculations and field‐emission scanning electron microscopy (FESEM) imaging show that Au‐NRs reach melting temperature after laser pulse exposure. Delivering femtosecond laser pulses directly onto the retina to treat retinoblastoma through the medium of the eye is possible without interacting with its compartments—making this treatment ideal for this type of cancer. This treatment methodology would be an invaluable tool for treatment of chemotherapy‐resistant and radiation‐resistant cancers. Abstract : A proof of principle for the treatment of retinoblastoma cancer using gold nanorods and femtosecond laser pulses is presented . With this technique, it is shown that selective targeting of retinoblastoma cells could be achieved. Astonishingly, a single treatment, requiring 20 femtosecond pulses (20 ms), results in 90% cell death.